PREDICTION OF FINANCIAL DISTRESS AS THE IMPACT OF THE COVID¬-19 PANDEMIC ON TRADE, SERVICES AND INVESTMENT COMPANIES IN INDONESIA USING ALTMAN Z-SCORE DISCRIMINANT ANALYSIS: (Study on the Indonesia Stock Exchange) - TRISNA SARY LEWARU; LINDA GRACE LOUPATTY (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This study aims to examine and analyze whether net working capital to total assets, retained earnings to total assets, EBIT to total assets, and book value of equity to book value of total debt partially and simultaneously have a significant effect on prediction of financial distress in corporate sector. trade, services and investments listed on the Indonesia Stock Exchange during the Covid-19 pandemic. The population in this study are all companies in the Trade, Services and Investment Sector listed on the Indonesia Stock Exchange in 2020. The sample used is 154 companies obtained using the saturated sampling technique (Census Technique). The independent variable (X) in this study is net working capital to total assets, retained earnings to total assets, EBIT to total assets, and book value of equity to book value of total debt, while the dependent variable (Y) is financial distress. This research data uses secondary data, namely the annual report of companies in the trade, services and investment sectors listed on the Indonesia Stock Exchange in 2020. The data analysis method used is Multivariate Discriminant Analysis (MDA) Altman Z-Score Model and Logistics Regression Test. The results showed that partially net working capital to total assets, retained earnings to total assets, EBIT to total assets, and book value of equity to book value of total debt had a negative and significant effect on financial distress. And simultaneously, net working capital to total assets, retained earnings to total assets, EBIT to total assets, and book value of equity to book value of total debt have a significant effect on financial distress.